Amitié sincère: En motberättelse och en historia om kärlek mellan kvinnor. En läsning av Karen Blixens »The roads round Pisa« - Lindén, Claudia (Tidskrift för litteraturvetenskap, 2010)
Amitié Sincère – a Counter Narrative and a Story of Love Between Women. A Reading of Karen Blixen’s/Isak Dinesen’s »The Roads Round Pisa« »The Roads Round Pisa« is the opening story in Karen Blixen’s debut work Seven Gothic Tales (1934). It is also one of her most remarkable stories and the one that most openly questions heterosexuality as a road to happiness. Blixen often works with an ironic, intertextual play with other texts, which takes the character of a counter narrative. Early on, both Ellen Moers and the Gothic scholar David Punter saw the connection between Blixen’s interest in the Gothic tradition and a gender critical attitude. In spite of Dinesen’s use of the Gothic this has not played any central role in the Dinesen reception. Modern researchers on the Gothic period, like Cyndy Hendershot, have pointed out how the disruption of stable notions of gender and sexuality is a characteristic of the genre. It is in this respect Blixen’s relation to the Gothic tradition should be investigated. Her texts are full of skeletons and ghosts, and with a focus on the fundamental instability of identity, gender and sexuality. In this article, which is part of a larger project on Blixen and the Gothic, I argue that, by connecting Blixen again to this disruptive Gothic tradition of transgressing gender we can also change our way of reading her. Where earlier feminist readings have looked for feminist representations in Blixen, I suggest a change of focus, to how intertextual »genre trouble« also produces »gender trouble.« Blixen’s feminism works through criticism and irony. Through a reading of »The Roads Round Pisa«, I will show how the Gothic and the gender criticism work together in an intertextual play with two classical Gothic texts; Mary Shelley’s Frankenstein and Sheridan Le Fanu’s Carmilla, to tell a story of love and loyalty between women.